Cell Cycle Commitment and the Origins of Cell Cycle Variability - Brooks, Robert F. (Frontiers in Cell and Developmental Biology, 2021)
Exit of cells from quiescence following mitogenic stimulation is highly asynchronous, and there is a great deal of heterogeneity in the response. Even in a single, clonal population, some cells re-enter the cell cycle after a sub-optimal mitogenic signal while other, ostensibly identical cells, do not, though they remain capable of responding to a higher level of stimulus. This review will consider the origins of this variability and heterogeneity. Particular attention will be paid to the role of two interacting molecular networks, namely the RB-E2F and APCCDH1 “switches”. These networks have the property of bistability and it seems likely that they are responsible for dynamic behaviour previously described kinetically by Transition Probability models of the cell cycle. The relationship between these switches and the so-called Restriction Point of the cell cycle will also be considered.